Accreditation of Medical Schools and its Repercussion within the Formation of Human Resources in Health - Piscoya Arbañil, José (1998)
Currently, the public asks for higher guarantees regarding the capacity and entrustness of physicians involved with their care. This latter engage us with the accomplishment of some minimal outlines in order to assure an adequate practice of Medicine. We emphasize here the necessity of a certification that must preserve the capacity of the physician who works in our country. Moreover, we propose the conformation of a National System of Certification for the faculties of Medicine and its goals are pointed out. Besides, we made a review of certification patterns from other countries.